Validation of a Monte Carlo Framework for Out-of-Field Dose Calculations in Proton Therapy - De Saint-Hubert, Marijke; Verbeek, Nico; Bäumer, Christian; Esser, Johannes; Wulff, Jörg; Nabha, Racell; Van Hoey, Olivier; Dabin, Jérémie; Stuckmann, Florian; Vasi, Fabiano; Radonic, Stephan; Boissonnat, Guillaume; et al. (Frontiers in Oncology, 2022)
Proton therapy enables to deliver highly conformed dose distributions owing to the characteristic Bragg peak and the finite range of protons. However, during proton therapy secondary neutrons are created which can travel a long distance and deposit dose out-of-field. This out-of-field absorbed dose needs to be considered for radiation-induced secondary cancers which are particularly relevant in the case of pediatric treatments. Unfortunately, no method exists in clinics for the computation of the out-of-field dose distributions in proton therapy. To help overcome this limitation a computational tool has been developed based on the Monte Carlo code TOPAS. The purpose of this work is to evaluate the accuracy of this tool by comparison to experimental data obtained from an anthropomorphic phantom irradiation. An anthropomorphic phantom of a 5-year-old child (ATOM, CIRS) was irradiated for a brain tumor treatment in an IBA Proteus Plus facility using a pencil beam dedicated nozzle. The treatment consisted of three pencil beam scanning fields employing a lucite range shifter. Proton energies ranged from 100 to 165 MeV. A median dose of 50.4 Gy(RBE) with 1.8 Gy(RBE) per fraction was prescribed to the initial planned target volume (PTV), which was located in the cerebellum. Thermoluminescent detectors (TLD) were used to detect gamma radiation. Additionally, bubble detectors (BD-PND) were used for measuring neutrons. The Monte Carlo code TOPAS (version 3.6) was run reaching an average standard statistical uncertainty of less than 0.2% (coverage factor k=1) on all voxels scoring more than 50% of the maximum dose. Out-of-the-field doses showed absorbed doses that were 5 to 6 orders of magnitude lower than the target dose. The discrepancy between TLD data and the corresponding scored values in the Monte Carlo calculations involving proton and gamma contributions was on average 18%. The comparison between the neutron equivalent doses between the Monte Carlo simulation and the measured neutron doses was on average 8%. Organ dose calculations revealed the highest dose for the thyroid, which was 120 mSv, while other organ doses ranged between 18 mSv for lungs and 0.6 mSv for testes.